Effect of Feedstock and Catalyst Impurities on the Methanol‐to‐Olefin Reaction over H‐SAPO‐34. Issue 1 (29th November 2016) - Vogt, Charlotte; Weckhuysen, Bert M.; Ruiz‐Martínez, Javier
Abstract: Operando UV/Vis spectroscopy with on‐line mass spectrometry was used to study the effect of different types of impurities on the hydrocarbon pool species and the activity of H‐SAPO‐34 as a methanol‐to‐olefins (MTO) catalyst. Successive reaction cycles with different purity feedstocks were studied, with an intermittent regeneration step. The combined study of two distinct impurity types (i.e., feed and internal impurities) leads to new insights into MTO catalyst activation and deactivation mechanisms. In the presence of low amounts of feed impurities, the induction and active periods of the process are prolonged. Feed impurities are thus beneficial in the formation of the initial hydrocarbon pool, but also aid in the unwanted formation of deactivating coke species by a separate, competing mechanism favoring coke species over olefins. Further, feedstock impurities strongly influence the location of coke deposits, and thus influence the deactivation mechanism, whereas a study of the organic impurities retained after calcination reveals that these species are less relevant for catalyst activity and function as "seeds" for coke formation only. Abstract : Important impurities : The effects of feedstock and intrinsic impurities, such as ethanol and coke, on the methanol‐to‐olefins conversion over H‐SAPO‐34 is explored by UV/Vis spectroscopy and on‐line mass spectrometry. Feedstock impurities aid the formation of the initial hydrocarbon pool, but also form deactivating species through a competing mechanism. Intrinsic impurities function as "seeds" for coke formation.